Growth enhancement of sunchoke by arbuscular mycorrhizal fungi under drought condition - Nacoon, Sabaiporn; Ekprasert, Jindarat; Riddech, Nuntavun; Mongkolthanaruk, Wiyada; Jogloy, Sanun; Vorasoot, Nimitr; Cooper, Julia; Boonlue, Sophon (Rhizosphere, 2021)
Due to its increasing economical values, sunchoke is widely planted including in Northeast Thailand where insufficient water supply recurs. This work then aimed to investigate the efficiency of 5 different AMF species to enhance growth of sunchoke under drought stress conditions. Factorial experiments in a randomized complete block design (RCBD) were conducted with four replications under two conditions, a well-watered (WW) and a drought stress (DS). This result showed that Rhizophagus irregularis BM-2 g1, Glomus hoi KKU g3 and Rhizophagus aggregatus BM-3 g3, were the best AMF to enhance the growth and yield of sunchoke. We found that Glomus etunicatum UDCN52867 g5 less affected the growth of sunchoke when compared to the other Glomus spp. in this work. Different AMF species belonging to Glomales affected different plant growth parameters at different levels. This suggested a variety of plant growth promoting functions of Glomus spp. Moreover, Acaulospora mallea KKU-NBP-SB-2, isolated from Eucalyptus plants, did not significantly enhance the growth and yield of sunchoke under both WW and DS conditions. This suggested that plant-AMF symbiosis is a species-specific interaction. Detailed mechanisms of AMF and an application of a combination of AMF species with different functions to enhance sunchoke growth are worth investigating.